A super high-rate sulfidogenic system for saline sewage treatment. (1st November 2016) - Tsui, To-Hung; Chen, Lin; Hao, Tianwei; Chen, Guang-Hao
Abstract: This study proposes a novel approach to resolve the challenging issue of sludge bed clogging in a granular sulfate-reducing upflow sludge bed (GSRUSB) reactor by means of introducing intermittent gas sparging to advance it into a super high-rate anaerobic bioreactor. Over a 196-day lab-scale trial, the GSRUSB system was operated from nominal hydraulic retention time of 4-hr to 40-min and achieved the highest organic loading rate of 13.31 kg COD/m 3 ·day which is substantially greater than the typical loading of 2.0–3.5 kg COD/m 3 ·day in a conventional upflow anaerobic sludge bed reactor treating dilute organic strength wastewater. The average organic removal efficiency and total dissolved sulfide of this system were 90 ± 4.2% and 158 ± 28 mg S/L, while organics residual in the effluent was 34 ± 14 mg COD/L. The control stage (without gas sparging) revealed that the sludge bed clogging happened concomitantly with the significant drop in extracellular polymeric substance content of granular sludge, through relevant chemical measurements and confocal laser scanning microscopy analyses. On the other hand, compared with increasing the effluent recirculation ratio (from 1.4 to 5), the three-dimensional computational fluid dynamics modeling in combination with energy dissipation analysis demonstrated that the gas sparging (at a superficial gas velocity of 0.8 m s −1 ) can create a 23 times higher liquid shear as well as enhanced particle attrition. Overall, this study not only developed a super high-rate anaerobic bioreactor for saline sewage treatment, but also shed light on the role of intermittent gas sparging in control of sludge bed clogging for anaerobic bioreactors. Graphical abstract: Highlights: Intermittent gas sparging was applied to resolve sludge bed clogging in GSRUSB. 90% COD removal was achieved under a high loading rate of 13.31 kg COD/m 3 ·day. EPS content of granules dropped significantly at the stage without gas sparging. Biofilm overgrowth on granules' surface was revealed as the determining factor. Gas sparging effectively created surface shear stress for the biofilm detachment.